Circulating Genotypes of Rotavirus Prior to Rotarix?vaccine Introduction in Kathmandu, Nepal - Shrestha, Sony; Thakali, Ocean; Raya, Sunayana; Sherchan, Samendra; Shrestha, Laxman; Parajuli, Keshab; Sherchand, Jeevan Bahadhur (Journal of Nepal Health Research Council, 2021)
Background: In Nepal, it is estimated that about 3 million children under 5 years of age are prone to diarrhea and previous studies have shown rotavirus as the major etiological agent. Given the high burden of rotavirus, Rotarix® vaccine was introduced in the national immunization schedule in July 2020. This study was carried out in a tertiary health center from January- September 2018 to determine the burden of rotavirus diarrhea as well as genotypic variations in the circulating virus prior to vaccine introduction in Kathmandu, Nepal.Methods: Hospital based cross sectional study was conducted among children less than 5 years of age attending Kanti Children’s Hospital. Rotavirus antigen detection was performed by enzyme immunoassay using ProSpecT Rotavirus Microplate Assay. Rotavirus A positive samples were further confirmed by genotyping using Reverse-Transcription Polymerase Chain Reaction.Results: A total of 530 children that included 184 males and 346 females were enrolled in this study. Rotavirus antigen was detected in 112 (21.1%) stool samples. Of the total 112 positive EIA stool samples that were genotyped, G12P[6] (30.3%) was found to be the most common type, followed by G3P[8] (26.8%), mixed type (14.3%), and G1P[6] (13.4%). Conclusions: Continued surveillance should be carried out nationwide in Nepal to understand the effectiveness of the vaccination program and to report any new trends in the circulating genotypes.Keywords: Children under five years of age; diarrhea; Nepal; rotavirus strains; RT_PCR